Comparative genome analysis of patulin-producing Penicillium paneum OM1 isolated from pears - Wencai Zhao; Sung-Yong Hong; Ae-Son Om (PeerJ)
Background The filamentous fungus Penicillium paneum (P. paneum) produces patulin as a toxic secondary metabolite (SM) on apples and pears. Little is known about the biosynthetic gene clusters (BGCs) of SMs, including patulin in P. paneum. Methods In this study, we sequenced the whole genome of P. paneum (isolate OM1), a patulin producer isolated from pears, and analyzed the genome sequence to identify its SM BGCs and compare its patulin BGC with those in other patulin-producing strains. In addition, we investigated the genes that encode carbohydrate-active enzymes (CAZymes) in P. paneum OM1, which play important roles in the degradation of plant cell walls, and analyzed the phylogenetic relationships among P. paneum OM1 and other closely related Penicillium species. Results The genome of P. paneum OM1 was estimated to be approximately 27.16 Mb with four chromosomes. Gene Ontology analysis using 7,098 functionally annotated proteins showed that genes involved in fungal defense mechanisms, such as SM biosynthesis, are enriched in the genome of P. paneum OM1. Of the 7,098 functionally annotated proteins from the genome, we identified 370 putative CAZymes. A phylogenetic analysis revealed that P. paneum OM1 has an evolutionarily close relationship with Penicillium chrysogenum (isolate Wisconsin 54-1255, a penicillin-producing strain) and Penicillium digitatum (isolate Pd1, a citrus fruit pathogen). We also identified a total of 33 SM BGCs, including a patulin BGC in P. paneum OM1. Moreover, the functional conservation analyses on all 15 patulin biosynthetic genes showed that each gene in P. paneum OM1 shares a high degree of sequence identity (above 73% identity) at both nucleotide and amino acid levels with the corresponding genes in four other patulin-producing Penicillium strains, while it shares a relatively low degree of identity (0-93%, identity, 0 and 60% as medians for amino acid sequence identity) with those in two non-patulin producing Penicillium species. Conclusions Our study improves understanding about BGCs of SMs, including patulin in P. paneum OM1, which causes blue mold rot on pome fruits. These data could provide the genetic basis of patulin biosynthesis in P. paneum OM1 to develop effective strategies for reducing patulin contamination on pome fruits.